A Holistic Approach Through Panchakarma in Management of Sarvanga Vata (AYUSHDHARA, 2025)
Sarvangavata is a type of Vatavyadhi which may be caused due to Kevala vata or Samsrushta vata and is characterized by Cheshtanivrutti (motor deficit /weakness), Vak stambha (dysarthria), Sira snayu shoshana (degeneration of nerve cells/axons/muscle wasting/flaccidity), Pada sankocha. Case report: of A 25-year-old female patient presented with a 4-year history of progressive weakness and wasting in all four limbs, resulting in difficulty walking without support, imbalance, generalized heaviness and weakness altered gait, slurred speech is explained here. Methodology: Treatment modalities like Sarvanga Agnichikitsa lepa, Koshta shodhana with Nimbamritadi eranda taila f/b Sarvanga Abhyanga, Shashtikashali pinda sweda, Sahacharadi ksheera basti and Shamana chikitsa were given. Conclusion: Patient showed significant improvement in the symptoms through the combined effects of Panchakarma and Shamanoushadhis.